Association between loop diuretic dose administered in first 24 hours of heart failure admissions and length of hospital stay. Issue 4 (4th July 2018) - Elashery, Ahmad Ramy; Aykent, Kazim; Kurdi, Hussam; Ibrahim, Mohammed; He, Shiquan; Petrini, Joann R; Kramer, Harvey M
ABSTRACT: Background : Heart failure remains one of the highest disease burdens in the USA and worldwide. Heart failure guidelines recommend starting with a higher or equal to home dose of loop diuretics in acute decompensated heart failure admissions. To date, no study has been published assessing the effect of first 24 h loop diuretic dose on length of hospital stay. Objective: We hypothesize that the higher the first 24 h loop diuretic dose to home dose ratio, the shorter the length of hospital stay will be. Design/Methods : Retrospective chart review was conducted in a community teaching hospital and included patients discharged between February, 2015 and April, 2016, with a primary diagnosis of acute decompensated heart failure. The primary outcome was the length of hospital stay. The study population was divided into three groups based on the hospital to home dose ratio. Results : Among the 609 patients included in the data analysis, there was no statistically significant difference in length of hospital stay among the study groups. Inpatient mortality and incidence of acute kidney injury were highest in the group that received a first-24-hours hospital dose that was less than their home dose. Percentage of weight loss and 30-day readmission were not statistically significantly different among the groups. Conclusion : There was no association between the dose ratio and length of hospital stay in each group. Additional randomized controlled trials need to be conducted to provide more evidence and guidance for dosing loop diuretics in acute decompensated heart failure admissions.